2021
DOI: 10.1007/s10311-021-01282-z
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic additives to increase methane generation during anaerobic digestion of livestock manure: a review

Abstract: Recycling livestock manure provides energy and prevent pollution, yet actual transformation processes are limited in terms of performance and cost. Here we review inorganic additives used to improve anaerobic digestion. Additives include minerals such as zeolite and magnetite, metals such as bulk and nanoparticles, industrial wastes; and pH-regulating additives. We focus on microbial mechanisms in terms of microbial growth, enzymes, interspecies electron transfer and microbial community, instead of the often r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 96 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Another inorganic additive that, in recent decades, has gained interest as an additive in anaerobic digestion and has been also used in the anaerobic digestion of primary sewage sludge is zero-valent iron (ZVI). ZVI which is a non-toxic and cost-effective metal monomer [65]. It has been reported that with the addition of ZVI into an anaerobic digester, more organics can directly be hydrolyzed and fermented into acetate due to its ability to serve as an electron donor in microbial metabolism [66].…”
Section: Minerals and Nanometal Particles In The Anaerobic Digestion ...mentioning
confidence: 99%
“…Another inorganic additive that, in recent decades, has gained interest as an additive in anaerobic digestion and has been also used in the anaerobic digestion of primary sewage sludge is zero-valent iron (ZVI). ZVI which is a non-toxic and cost-effective metal monomer [65]. It has been reported that with the addition of ZVI into an anaerobic digester, more organics can directly be hydrolyzed and fermented into acetate due to its ability to serve as an electron donor in microbial metabolism [66].…”
Section: Minerals and Nanometal Particles In The Anaerobic Digestion ...mentioning
confidence: 99%
“…FeNPs have been investigated in most of the studies in the area of AD of biomass and subsequent biogas production [ 154 ]. Fe-based additives were reported to influence microbial activity during AD [ 154 , 166 , 169 ]. Yang et al [ 170 ] performed microbial diversity analysis (nZVI supplemented AD of swine manure) and found an abundance of hydrogenotrophic Methanomassiliicoccus (39.2–92.0%).…”
Section: Solutionsmentioning
confidence: 99%
“…Food waste is almost free from emerging contaminants; however, biogas productivity from anaerobic digestion of food waste as a standalone substrate is quite low (Chew et al 2021;Liu et al 2021b). The bioenergy productivity is highly increased by anaerobic digestion of food waste with co-substrate, i.e., agricultural, biosolids or sludge, and manures.…”
Section: Anaerobic Digestion Of Sludges Containing Emerging Contaminantsmentioning
confidence: 99%